67 EVALUATION OF A 12-LEAD DIGITAL HOLTER SYSTEM FOR 24-HOUR Q-T INTERVAL ASSESSMENT. (1st March 2006) - Somberg, J. C.; Molnar, Z.; Ranade, V.; Cvetanovic, I.; Molnar, J.
Abstract : Background: Drug-induced Q-T prolongation may precipitate life-threatening cardiac arrhythmias; therefore, evaluation of the Q-T prolonging effect of new pharmaceutical agents in a "thorough Q-T/Q-Tc study" is being mandated by the FDA. The purpose of this study was to evaluate the feasibility of a 12-lead digital Holter system for a thorough Q-T/Q-Tc study. Methods: Five healthy volunteers underwent 24-hour digital Holter monitoring (NorthEast Monitoring, Maynard, MA). The system provides automated Q-T analysis (AQA) and the option of onscreen manual over read (MOR) of automatic Q-T determinations. Each recording underwent a fully AQA followed by an onscreen complete MOR by an expert observer. The MOR was used as the reference standard for the validation of AQA. Each recording underwent a second analysis at 2 weeks following the first analysis to evaluate reproducibility. The effect of data sampling (5-min segment/hour), the system sensitivity to detect 5 ms increase in Q-T, and the ability to assess circadian variation were also evaluated. Results: The fully AQA resulted in identical QT for the first and second analyses, but with obvious errors in Q-T measurements. Compared to the complete onscreen MOR, the 24-hour mean Q-T was longer with AQA (416 ± 41 vs 387 ± 30 ms, p < .001, r = .3). The reproducibility of automatic analysis with complete MOR was very good (Q-T: 387 ± 30 vs 387 ± 30 ms), coefficient of variation (CV) = 0.2%, r = .986, p < .001. The 5-minute mean Q-T intervals correlated well with the hourly mean Q-T intervals (r = .994, p < .001, CV = 1 ms) and both showed a similar circadian variation. The system was sensitive to detect a 5 ms change in Q-T intervals (5 ± 2 ms, CV = 0.6%, r = .998, p < .001). Conclusions. The fully automatic Q-T analysis is not an acceptable method, while the automatic analysis with MOR is a highly sensitive and reproducible method. Data sampling by analyzing 5-minute segments per hour is also sensitive and reproducible. The 12-lead digital Holter technique is suitable for Q-T analysis and may have advantage compared to the serial recordings of large number of standard 12-lead ECGs in the evaluation of drug effects on the Q-T interval.